Analysis of landslide prediction as related to landuse changes in Perlis / Nur Syahira Rashid - Rashid, Nur Syahira (2018)
The increaseness of development and agricultural activities will become a very significant contributor towards landslide and soil loss. The aim of this study is to analyse the landslide prediction and rate of soil loss as related to landuse changes in Perlis. The study area; Perlis is covered with 77.4% agriculture, 18% of forest, 3.2% urbanization and 1.5% water bodies in 1999. However, during the year 2015; the agriculture area and forest decrease to 62% and 15% respectively. Meanwhile, urbanization increase to 19.5% and water bodies 2.03%. These two results fi-om image classification were then simulated using LandslideSim to evaluate potential area of landslide. Based on the evaluation indicates that no area in Perlis potential of landslide. However, the rate of soil loss in Perlis increase fi-om year 1999 to 2015. Where the higher rate of soil loss in Perlis in 1999 is 3.86% and increase to 4.76% in 2015. These show that landuse changes had gave a big impacts towards rate of soil loss. This statement is showed in correlation analysis between forest, agriculture, urbanization and water bodies with rate of soil loss. Forest and agriculture area have a strong negative correlation with soil loss which show high correlation value ( R 2 = 0.9905 (forest with rate of soil loss) and R^=0.9778 (agriculture with rate of soil loss). Meanwhile, urbanization and water bodies area have a strong positive correlation with soil loss which show high correlation value (R^= 0.9973 (urbanization with rate of soil loss and R^=0.9619 (water bodies with rate of soil loss). These result indicates that changes of land use especially when vegetation area decrease and urbanization area increase are linear with the soil loss in Perlis.